The Theoretical Aspects of Credit Risk Assessment and Management in Banks Amid Economic Instability - Pavlenko Liudmyla D.; Krukhmal Olena V.; Popova Kristina E. (Bìznes Inform, 2025)
The article summarizes the main approaches to defining the essence, assessment and management of credit risks of a bank. Based on the analysis of domestic and foreign publications, the authors propose to define credit risk as the probability that a borrower (individual or legal entity) will not fulfill its obligations to the bank in full and on time in accordance with the signed loan agreement. Clustering of scientific research on the bank's credit risk was carried out. According to the clustering results, the bulk of scientific papers are focused on the following areas: the relationship of credit risk assessment to financial markets (yellow cluster), the banking sector and financial crises (red cluster), machine learning methods (green cluster), risk management and analysis (blue cluster), and insurance and risk forecasting (purple cluster). The reasons for the existence of credit risk are identified. The components of a modern credit risk management system are outlined, which include credit risk management policies and regulations, lending regulations, information infrastructure, the process of identifying loans with deteriorated quality, work with problem assets, preparation and submission of periodic reports to the bank's management and supervisory board, and the function of independent inspections of lending activities. The risk map of the banking sector is analyzed in accordance with the NBU methodology. The key aspects of banking risk assessment are highlighted, the approaches and stages of determining the amount of a bank's credit risk are revealed, in particular, banks calculate the amount of a debtor's credit risk using an individual, group or simplified assessment approach, and the choice of approach depends on the characteristics of the loan and the borrower. The article estimates the values of prudential ratios H7, H8, H9 for the Ukrainian banking system from 2020 to January 2025.